THE ARTISTIC AND SCIENTIFIC EVOLUTION OF THE ORIGAMI: A theoretical and practical study on the practice and techniques of folds (Palíndromo, 2017)
This article aims to understand how origami was inserted in classrooms and art galleries and then become a major paradigm of technological innovation, especially within sustainability. For such study, a historical review is made based on the trajectory of three artists: Josef Albers, Ronald Resch and Lygia Clark. Investigating the professional evolution of each one, it is noticed that many professional works and multidisciplinary investigations are inspired in these modern figures. Studying aspects initially pointed out by the three artists directly or indirectly, the origami components are analyzed such as valley folds, mountain folds, crease pattern and adapted origami design. To complement the study, an experimental application of a bag prototype is done reusing used materials; the objective is the practical proof of origami techniques indicated by the study, joining the principle of folds with sustainability.
Keywords: origami; innovation; art; sustainability; crease pattern